Lay review of the South London and Maudsley NHS Foundation Trust’s (SLaM) Clinical Records Interactive Search (CRIS) system website to better meet UK Heath Data Research Alliance Transparency Standards. - Jewell, Amelia; Woods, Hannah; Morrow, Liz; Booth, Alex; Davenport, Franca; Stewart, Robert (International Journal of Population Data Science, 2024)
Background The South London and Maudsley NHS Foundation Trust (SLaM) is one of the largest providers of secondary mental healthcare in Europe. In 2007, SLaM developed the Clinical Record Interactive Search (CRIS) system which provides authorised researchers with regulated, secure access to anonymised information extracted from SLaM’s electronic clinical records system1. CRIS has been very successful as a research data resource and has supported over 300 peer reviewed publications over its 15+ years of operation. The CRIS website (www.maudsleybrc.nihr.ac.uk/facilities/clinical-record-interactive-search-cris) was developed to provide information to SLaM service users, the general public, and prospective research users. The website includes information on what CRIS is, approved CRIS projects and publications resulting from CRIS projects, as well as detailed information on data linkages involving CRIS and on Natural Language Processing (NLP) algorithms as a resource. The website is the main source of information available to academic users prior to meeting with a member of the CRIS Team and is a large component of the wider CRIS communications plan which aims to ensure that all potential CRIS stakeholders can access relevant information about CRIS in several different formats. Introduction We planned to conduct a lay review of the CRIS webpages involving both SLaM service users, carers, and CRIS academic users. The lay review was designed to support with alignment against the following UK Heath Data Research Alliance (HDRA) Transparency Standards2: Standard 1: Open access application form and guidance Standard 2: Transparent application process and criteria Standard 3: Clear website navigation Standard 4: Consider Target Audience Methods A lay review of the website was conducted with a group of five mental health service users and carers. The review was conducted in two stages, firstly, an individual in-depth review of two webpages per person with an online questionnaire, followed by a focus group. An academic review by two junior researchers was also conducted, this involved a review of the webpages and completion of an online questionnaire. Results The online questionnaires and focus group suggested several improvements to the website. Feedback on each page was reviewed and compared against the UK HDRA Transparency Standards. A list of changes was drafted in consultation with communications colleagues. Changes were made to pages, including updating images, adding additional information, making accessibility changes, and adding a new page specifically aimed at service users and the public. Service user consultees were sent a further online questionnaire to provide feedback on the updated pages. Feedback was positive. Conclusions There were challenges involved in designing a website that was informative to both lay public readers and potential research users. Following the lay review and subsequent changes to the CRIS website, the website better meets the UK HDRA Transparency Standards. References Perera, G., Broadbent, M., Callard, F., Chang, C-K., Downs, J., Dutta, R., Fernandes, A., Hayes, R.D., Henderson, M., Jackson, R., Jewell, A., Kadra, G., Little, R., Pritchard, M., Shetty, H., Tulloch, A. and Stewart, R. (2016) Cohort profile of the South London and Maudsley NHS Foundation Trust Biomedical Research Centre (SLaM BRC) Case Register: current status and recent enhancement of an Electronic Mental Health Record-derived data resource. BMJ Open, 6:e00872. Macaulay, Y., UK Health Data Research Alliance., Pan-UK Data Governance Steering Group., HDR UK Public Advisory Board., Five Safes Action Force. (2023) Pan-UK Data Governance Steering Group Data Access Transparency Standards. Available from: https://zenodo.org/records/8262453. [Accessed 23.04.2024]